Current Understanding of Cardiac Troponins Metabolism: A Narrative Review - Michailovich Chaulin, Aleksey (Current Medicinal Chemistry, 2022)
Background and Aims: Current methods (highly sensitive and ultra-sensitive) of cardiospecific troponins detection have enabled early diagnosis of myocardial infarction (MI) and selection of optimal treatment tactics for patients early from admission. The use of these methods in real clinical practice helps to choose the most optimal treatment tactics for patients in the early stages after admission, and this significantly improved the further prognosis of patients suffering from MI. However, there are a number of problems that arise when using highly sensitive or ultra-sensitive methods for determining cardiospecific troponins: frequent and unexplained increases in serum levels of cardiospecific troponins in a number of pathological conditions unrelated to MI; insufficient knowledge and understanding of the mechanisms of release and increase in the levels of cardiospecific troponins; poorly understood features and mechanisms of circulation and elimination of cardiospecific troponins; the presence of conflicting information about the influence of several factors (gender, age and circadian characteristics) on the levels of cardiospecific troponins in blood serum; undisclosed diagnostic potential of cardiospecific troponins in non-invasive human biological fluids. These problems cause great difficulties and increase the risk of errors in the differential diagnosis of MI, and also do not allow to fully unlock the diagnostic potential of cardiospecific troponins. In general, these problems are associated with a lack of understanding of the fundamental mechanisms of the metabolism of cardiospecific troponins. The main purpose of this narrative review is to summarize and provide detailed information about the metabolism of cardiospecific troponins and to discuss the potential impact of metabolic features on the diagnostic value of cardiospecific troponins and their diagnostic capabilities. Materials and Methods: This narrative review is based on the analysis of publications in the Medline, PubMed, and Embase databases. The terms “cardiac troponins”, “troponin T”, and “troponin I” in combination with “mechanisms of increase”, “mechanisms of release”, “circulation”, “proteolytic cleavage”, “elimination”, “circadian rhythms”, “saliva”, and “urine” were used to search publications. Results: It has been reported that the metabolic features (mechanisms of release, circulation, and elimination) of cardiospecific troponins may have an important influence on the diagnostic value of cardiospecific troponins in a number of physiological and pathological conditions that cause cardiomyocyte damage. The main mechanisms of cardiac troponin release are: cardiomyocyte apoptosis; myocardial cell regeneration and renewal; increased cell membrane permeability; release of troponins by vesicular transport; increased proteolytic degradation of cardiospecific troponin molecules within the cell which may facilitate their release from intact myocardial cells or in the initial phase of those pathological conditions that increase the activity of enzymes that degrade cardiospecific troponins. Besides, the formation of small fragments (troponin molecules) may facilitate their penetration into other body fluids such as urine and/or oral fluid which may provide researchers and practitioners with a new diagnostic opportunity. It should be noted that in addition to release mechanisms, cardiospecific troponin elimination mechanisms may play an important diagnostic role. The contribution of release and elimination mechanisms to different pathologies may differ significantly. Circadian rhythms of cardiospecific troponins may be associated with fluctuations in the activity of those organ systems which influence the mechanisms of cardiospecific troponin release or elimination. Such major systems include: neuroendocrine, urinary, and hemostasis. Conclusion: Cardiospecific troponins metabolism has an important influence on diagnostic value and diagnostic capabilities. Further study of the features of cardiac troponin metabolism (mechanisms of release, circulation and elimination) is required to improve diagnosis and differential diagnosis of diseases causing cardiomyocyte damage. The data on the influence of circadian rhythms of cardiospecific troponins on the diagnostic value and the possibility of determining cardiospecific troponins in body fluids that can be obtained by noninvasive methods are very interesting. However, so far this information and valuable capabilities have not been applied in clinical practice because of the paucity of studies conducted.
Keywords: circadian rhythms